Extreme weather and societal impacts in the eastern Mediterranean - A. Hochman; A. Hochman; F. Marra; G. Messori; G. Messori; J. G. Pinto; S. Raveh-Rubin; Y. Yosef; G. Zittis (Earth System Dynamics, 2022)
Gaining a holistic understanding of extreme weather, from its physical drivers to its impacts on society and ecosystems, is key to supporting future risk reduction and preparedness measures. Here, we provide an overview of the state of the art, knowledge gaps and key open questions in the study of extreme weather events over the vulnerable eastern Mediterranean. This region is situated in a transition zone between subtropical and mid-latitude climates. The large-scale atmospheric circulation and its interaction with regional synoptic systems (i.e., Cyprus Lows, Red Sea Troughs, Persian Troughs, “Sharav” Lows) and high-pressure systems mainly govern extreme weather. Complex orographic features further play an important role in the generation of extreme weather. Most extreme weather events, including heavy precipitation, cold spells, floods and windstorms, are associated with Cyprus Lows or active Red Sea Troughs, whereas heat waves are related with either Persian Troughs and sub-tropical high-pressure systems in summer or the Sharav Low during springtime. In future decades, heat waves and droughts are projected to significantly increase in both frequency and intensity. Changes in heavy precipitation may vary in sign and magnitude depending on the scale, severity and region of interest. There are still relatively large uncertainties concerning the physical understanding and the projected changes of cold spells, windstorms and compound extremes, as these types of events received comparatively little attention in the literature. We further identify knowledge gaps that relate to the societal impacts of extreme weather. These gaps mainly relate to the effects extreme weather may have on mortality, morbidity and infrastructure in the eastern Mediterranean. Research is currently limited in this context, and we recommend strengthening the database of analyzed case studies. We trust that this can only be suitably accomplished by inter-disciplinary and international regional collaboration (in spite of political unrest).